PENANAMAN NILAI NASIONALISME DALAM PEMBELAJARAN PPKn PADA SISWA KELAS V SDN BULU - Erlytasari, Alvina; Sukartono, Sukartono (STIT AL MULTAZAM, 2023)
The attitude of nationalism must be instilled in every citizen from the earliest possible age because due to the influence of globalization and the rapid progress of the times, concerns about the fading of nationalism in the nation's generation are becoming increasingly clear. By instilling the value of nationalism in Civics learning, it provides space and a place for teachers to instill nationalist values in students as much as possible at every opportunity starting from the introduction of learning to closing. This study aims to describe the strategies for instilling nationalist values, as well as the obstacles and their solutions. This study uses a descriptive qualitative method. Data collection was carried out using observation techniques, interviews,s and documentation. Test the validity of the data using triangulation of sources and techniques. The data analysis technique uses Miles and Huberman's interactive analysis with the stages of data reduction, data presentation, and drawing conclusions. The results of this study say that the role and strategy of teachers and schools in instilling nationalist values is quite good, the management of obstacles is also excellent thanks to the teacher's experience and ability to find solutions.Â